Sustainability in closed and open economies - Gernot Klepper; Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This paper discusses unilateral sustainability policies for tradable resources in closed and open economies. The effects of sustainability policies are modelled in an intertemporal, competitive framework by applying different sustainability rules which are introduced unilaterally in the domestic country. The paper shows that no sustainability rule will lead to a slower rate of extraction of the resource. Instead, resource extraction is increased in both countries. It is also shown that the foreign country may well gain in terms of consumption and real income from such unilateral sustainability policies but not in terms of sustainability.
Keywords: 330; International trade; factor mobility; sustainability; international environmental problems